1994
DOI: 10.1017/s0950268800051542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum IgG antibodies to Puumala virus (haemorrhagic fever with renal syndrome) in Northern Sweden

Abstract: SUMMARYA stratified and randomly-selected population sample was identified in 1990 in order to study the seroprevalence of nephropathia epidemica (haemorrhagic fever with renal syndrome) in Northern Sweden. Sera from 1538 subjects (750 men, 788 women), 25-64 years of age, were analysed for the presence of Puumala virus (PUV) specific-IgG by the indirect immunofluorescence antibody test. Specific IgG was detected in sera from 83 subjects (54%). Men and women had similar seroprevalence rates. The highest seropre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 17 publications
9
55
4
Order By: Relevance
“…The presence of Puumala vilus antibodies did not significantly correlate with age (P=0.30). This finding is in contrast to the results of a previous investigation of arandomized and stratified adult population in which the seroprevalence was found to increase with age (12). It should be recalled, however, that our material comprised subjects of a relatively narrow age interval.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…The presence of Puumala vilus antibodies did not significantly correlate with age (P=0.30). This finding is in contrast to the results of a previous investigation of arandomized and stratified adult population in which the seroprevalence was found to increase with age (12). It should be recalled, however, that our material comprised subjects of a relatively narrow age interval.…”
Section: Resultscontrasting
confidence: 97%
“…In a randomized and stratified study from northern Sweden, a 9% prevalence of Puumala virus antibodies was found for the adult population. Farmers and forestry workers had an increased prevalence (12,13). It could not be discerned, however, whether the difference was due to occupation or to the workers' mral living only.…”
mentioning
confidence: 93%
“…The present study found no significant difference in seroprevalence by sex, similar to a number of other reports, although the male:female ratio of clinical 'epidemic nephropathy' cases may not be 1 : 1, and in Russia was reported as 5 : 1 [6,17,19,20].…”
Section: Serological Study Of Human Hantavirus Infection 863supporting
confidence: 90%
“…The pattern of age-related seroprevalence rates reported here is similar to those from other European studies, e.g., Sweden [19], with the highest prevalence at age 55-74 years. Antibodies against hantavirus remain detectable for decades after infection [16,21] and, therefore, a progressive increase in seroprevalence is to be expected.…”
Section: Serological Study Of Human Hantavirus Infection 863supporting
confidence: 89%
“…The predominant species in Western and Northern Europe is Puumala virus (PUUV). It causes nephropathia epidemica (NE), a mild form of haemorrhagic fever with renal syndrome (HFRS) [2][3][4][5][6]. Typical symptoms are fever, headache, muscle pain, nausea and impaired renal function [7,8].…”
Section: Introductionmentioning
confidence: 99%